Epitranscriptome profiles reveal participation of the RNA methyltransferase gene OsMTA1 in rice seed germination and salt stress response - Yingbo Li; Ming Yin; Juan Wang; Xiuqin Zhao; Jianlong Xu; Wensheng Wang; Binying Fu (BMC Plant Biology)
Abstract Background RNA m6A methylation installed by RNA methyltransferases plays a crucial role in regulating plant growth and development and environmental stress responses. However, the underlying molecular mechanisms of m6A methylation involved in seed germination and stress responses are largely unknown. In the present study, we surveyed global m6A methylation in rice seed germination under salt stress and the control (no stress) using an osmta1 mutant and its wild type. Results The knockout of OsMTA1 resulted in a decreased level of m6A methylation and delayed seed germination, together with increased oxidative damage in the osmta1-1 mutant, especially under salt stress, indicating that OsMTA1 performs a crucial function in rice seed germination and salt stress response. Comparative analysis of m6A profiling using methylated RNA immunoprecipitation sequencing revealed that a unique set of genes that functioned in seed germination, cell growth, and development, including OsbZIP78 and OsA8, were hypomethylated in osmta1-1 embryos and germinating seeds. Numerous genes involved in plant growth and stress response were hypomethylated in the osmta1-1 mutant during seed germination under salt stress. Further combined analysis of the m6A methylome and transcriptome revealed that the loss of function of OsMTA1 had a more complex impact on gene expression in osmta1-1. Several hypomethylated genes with a negative role in growth and development, such as OsHsfA7 and OsHDAC3, were highly up-regulated in the osmta1-1 mutant under the control condition. In contrast, several hypomethylated genes positively associated with stress response were down-regulated, whereas a different set of hypomethylated genes that functioned as negative regulators of growth and stress response were up-regulated in the osmta1-1 mutant under salt stress. These results further demonstrated that OsMTA1-mediated m6A methylation modulated rice seed germination and salt stress response by regulating transcription of a unique set of genes with diverse functions. Conclusion Our results reveal a crucial role for the m6A methyltransferase gene OsMTA1 in regulating rice seed germination and salt stress response, and provide candidate genes to assist in breeding new stress-tolerant rice varieties.